Health-Related Quality of Life in Early-Onset Scoliosis Patients Treated Surgically: EOSQ Scores in Traditional Growing Rod Versus Magnetically Controlled Growing Rods. Issue 2 (15th January 2018) - Doany, Michael E.; Olgun, Z. Deniz; Kinikli, Gizem Irem; Bekmez, Senol; Kocyigit, Aykut; Demirkiran, Gokhan; Karaagaoglu, A. Ergun; Yazici, Muharrem
Abstract : Study Design: Cross-sectional study. Objective: To compare quality of life and caregiver burden in traditional growing rod (TGR) and magnetic controlled growing rods (MCGR) patients. Summary of Background Data: MCGR decrease surgical sessions associated with treatment of early onset scoliosis (EOS), hoping to minimize the burdens seen with repetitive invasive surgeries in TGR treatment. Although the clinical indications for these treatments have largely been agreed upon, there is a lack of understanding of their impact on patients' and families' quality of life. Methods: Inclusion criteria: ⩽10 years of age at index procedure, major curve ≥30°, no previous spine surgery, minimum 1-year postoperative follow-up. The previously validated 24-item early onset scoliosis questionnaire (EOSQ-24) was utilized to assess quality of life. Statistic methods were applied to compare domain scores between TGR and MCGR patients. Results: Forty-four children with EOS were enrolled; 25 TGR and 19 MCGR. Groups were similar in sex and age at index surgery. Age at time of questionnaire and mean length of follow-up were significantly different; patients were older (14.0 vs. 8.8 yr) and had longer follow-up (101.3 vs. 34.3 mo) in TGR ( P  < 0.01). Deformity correction and complication rates were similar between groups. At the time of questionnaire, scores of economic burden and overall satisfaction in MCGR were significantly superior to those in TGR by univariate analysis. When controlled for duration of follow-up, some domain scores trended towards statistical significance, some remained stable, and others regressed to non-significance. Conclusion: Health related quality of life data reveal superior outcomes in overall satisfaction and financial burden domains in the MCGR group. However, the positive effects of MCGR decrease when controlled for length of follow up, indicating that the MCGR is not yet a magic fix-all, and that the TGR remains an option in the treatment of EOS. Level of Evidence: 3